Avaliação do petróleo por termogravimetria para simulação de curva PEV, fator de caracterização e resíduo de carbono - Ribeiro, Marcilio Pelicano (2014)
Petroleum evaluation is analyze it using different methodologies, following international standards to know their chemical and physicochemical properties, contaminant levels, composition and especially their ability to generate derivatives. Many of these analyzes consuming a lot of time, large amount of samples , supplies and need an organized transportation logistics, schedule and professionals involved. Looking for alternatives that optimize the evaluation and enable the use of new technologies, seven samples of different centrifuged Brazilian oils previously characterized by Petrobras were analyzed by thermogravimetry in 25-900° C range using heating rates of 05, 10 and 20ºC per minute. With experimental data obtained, characterizations correlations were performed and provided: generation of true boiling point curves (TBP) simulated; comparing fractions generated with appropriate cut standard in temperature ranges; an approach to obtain Watson characterization factor; and compare micro carbon residue formed. The results showed a good chance of reproducing simulated TBP curve from thermogravimetry taking into account the composition, density and other oil properties. Proposed correlations for experimental characterization factor and carbon residue followed Petrobras characterizations, showing that thermogravimetry can be used as a tool on oil evaluation, because your quick analysis, accuracy, and requires a minimum number of samples and consumables